Operative Treatment of Nonprimary Osteochondral Lesions of the Talus: A Systematic Review - Correia Cardoso, R (2024)
Background: Nonprimary osteochondral lesions of the talus (OLT) pose a significant challenge in orthopaedics, with no definitive consensus on optimal surgical treatment. Purpose: To consolidate the most recent evidence on operative treatments for nonprimary OLT by assessing patient-reported outcomes (PROs), postoperative complications, and clinical failures. Study design: Systematic review; Level of evidence, 4. Methods: This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 and PRISMA in Exercise, Rehabilitation, Sport medicine and Sports science guidelines. Searches were conducted in PubMed, Embase, and Cochrane Library databases through June 2023. Eligible studies evaluated operative outcomes in skeletally mature patients with nonprimary OLT after failed previous surgeries. Primary outcomes included clinical and functional PROs. Secondary outcomes included postoperative complications and clinical failures. Quantitative analyses involved weighted means, mean differences, minimal clinically important differences, success rates (95% binomial proportion confidence interval), and a pre-to-postoperative meta-analysis. Results: Out of 3992 identified records, 50 studies involving 806 ankles from 794 patients were included. All operative treatments significantly improved PROs (P < .05), except osteochondral allograft transplantation (OCA) for American Orthopaedic Foot and Ankle Society and pain (visual analog scale/numeric rating scale [VAS/NRS]) scores and HemiCAP for pain (VAS/NRS) scores. Autologous chondrocyte implantation (ACI) and osteochondral autologous transplantation (OAT) demonstrated the greatest PRO success rates, exceeding 80%. Postoperative complications occurred in 4% of cases, most frequently with HemiCAP. Clinical failures affected 22% of cases, particularly with autologous matrix-induced chondrogenesis, OAT, OCA, and HemiCAP. Conclusion: Our systematic review demonstrated that ACI and OAT are promising treatments for nonprimary OLT, with ACI showing fewer clinical failures than OAT. Conversely, OCA and HemiCAP exhibited lower effectiveness and higher clinical failure rates, suggesting a need for reassessment.